ПРОБЛЕМИ ФОРМУВАННЯ В УКРАЇНІ МІНІМАЛЬНИХ ЗАПАСІВ НАФТИ ТА НАФТОПРОДУКТІВ (International Journal of Innovative Technologies in Economy, 2018)
The article analyzes the current state of the institutional environment for the creation of minimum oil and petroleum products reserves in accordance with the documents of the Association of Ukraine with the EU. In particular, the problems and prospects of the implementation of the plan of implementation of the European Directive 2009/119 / EU concerning the formation of stabilization oil and oil products, in which the draft model for the creation of oil and petroleum products reserves is presented.